International and Kazakhstan experience in issues of water security and water resources: institutional and regulatory aspects - Zhansautova, A.; Kazbekova, M. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2018)
The systematization of the UN approaches to water security is presented, key reports and publications on this subject are analyzed. The experience of foreign countries (Kenya, Saudi Arabia, Jordan, Ecuador, Israel, Turkey, etc.) in the issues of water resources regulation has been consolidated. Kazakhstan’s experience is characterized by the development of a regulatory framework, the availability of an authorized state body in the field of water resources and a vision of the problem of water security in the concept of transition to a green economy and foreign policy. At the same time, the issue of developing a state program of water security is actualized. At the present stage, new challenges have emerged due to the constant floods, which contribute to an increase in the amount of melt water. Therefore, a complex of measures is needed to improve institutions, government programs and legislation.